Fast and easy dimensioning of robust and sustainable filler beam bridges. Issue 4 (17th September 2019) - Rademacher, Dennis; Tilley, Neil
Abstract : Filler beam bridge construction with hot-rolled steel sections at close centres and filled with concrete meet all the requirements of small and medium span railway bridges. Therefore, filler beam bridges have been used for many years with considerable success, in particular where construction depth restrictions are relevant for the design. Moreover, they are perfectly suitable for use with high-speed railway lines. Since the late 1970s, various railway companies have established standard designs with guidelines, supplemented with calculation tables that correspond to their own rules. Some of these guidelines have become outdated with introduction of the Eurocodes. However, since on one hand there is a growing interest in this type of construction, and on the other hand a desire to economically evaluate large amounts of design data, hence there is a need for a calculation tool which enables quick, efficient and reliable designs. For this reason, new design tables for filler beam bridges in the German high-speed railway network up to 350 km/h have been developed, which enable the design engineer a quick and direct evaluation of all relevant cross-sectional data of single-track single-span bridges in the span range from 5 to 35 m - without costly statics. The tables and the software, with which the tables were generated, will be shown in the article.